An evaluation of quality of life among Cambodian adults living with HIV/AIDS and using antiretroviral therapy: a short report. Issue 12 (1st December 2016) - Yang, Youngran; Thai, Sopheak; Choi, Jongsan
ABSTRACT: The aim of this study was to evaluate quality of life (QOL) and analyze its determinants among Cambodian adults living with HIV/AIDS who are on antiretroviral therapy (ART). A cross-sectional study was conducted using convenience sampling to select 150 adults 18 years of age or older from the patient population at the HIV/AIDS care hospital in Phnom Penh, Cambodia. QOL was assessed using the World Health Organization Quality of Life HIV BREF; socio-demographic characteristics, time elapsed since HIV diagnosis, months on ART, CD4 cell count, family and community support, depression, and anxiety were included in the survey. Results of the multiple regression analysis indicate that positive predictors of QOL included being female, being less 40 years old, having a household monthly income greater than 300 USD, having an education beyond the secondary level, or being employed. However, time elapsed since HIV diagnosis and duration of ART were not significantly associated with QOL and CD4 cell count and the World Health Organization clinical stage had little association with QOL. Perceiving oneself as healthy and happy and reporting no depression or anxiety were associated with a positive QOL. These findings suggest the importance of group-specific interventions to improve the QOL for those people living with HIV/AIDS in Cambodia who are male, have a low household income or education level, are unemployed, or are anxious or depressed.